Skill formation under incomplete information - Philipp Weinschenk (Max Planck Institute for Research on Collective Goods, 2010)
We consider an economic model of child development with multiple stages. Due to incomplete information, parents are not able to tailor their investments to their child's type when the child is young. We show that incomplete information weakens the importance of early investments in children when inter-stage investments are easily substitutable, but strengthens them when substitution is difficult. The latter case is empirically relevant.
Keywords: I21; J13; D80; 330; Skill Formation; Education; Incomplete Information; Kinder; Bildungsinvestition; Unvollkommene Information; Eltern; Zeitökonomik; Theorie